A multifactorial anti‐cachectic approach for cancer cachexia in a rat model undergoing chemotherapy. Issue 1 (14th May 2015) - Toledo, Míriam; Penna, Fabio; Oliva, Francesc; Luque, Melania; Betancourt, Angelica; Marmonti, Enrica; López‐Soriano, Francisco J.; Argilés, Josep M.; Busquets, Sílvia
Abstract: Background: The effectiveness of drugs aimed at counteracting cancer cachexia is generally tested in pre‐clinical rodent models, where only the tumour‐induced alterations are taken into account, excluding the co‐presence of anti‐tumour molecules that could worsen the scenario and/or interfere with the treatment. Methods: The aim of the present investigation has been to assess the efficacy of a multifactorial treatment, including formoterol and megestrol acetate, in cachectic tumour‐bearing rats (Yoshida AH‐130, a highly cachectic tumour) undergoing chemotherapy (sorafenib). Results: Treatment of cachectic tumour‐bearing rats with sorafenib (90 mg/kg) causes an important decrease in tumour cell content due to both reduced cell proliferation and increased apoptosis. As a consequence, animal survival significantly improves, while cachexia occurrence persists. Multi‐factorial treatment using both formoterol and megestrol acetate is highly effective in preventing muscle wasting and has more powerful effects than the single formoterol administration. In addition, both physical activity and grip strength are significantly improved as compared with the untreated tumour‐bearing animals. The effects of the multi‐factorial treatment include increased food intake (likely due to megestrol acetate) and decreased protein degradation, as shown by the reduced expression of genes associated with both proteasome and calpain proteolytic systems. Conclusions: The combination of the two drugs proved to be a promising strategy for treating cancer cachexia in a pre‐clinical setting that better resembles the human condition, thus providing a strong rationale for the use of such combination in clinical trials involving cachectic cancer patients.